ANALISA AERODINAMIKA KENDALI CANARD ROKET RKX 250 - Ginting, Salam (Indonesian Journal of Aerospace, 2007)
In the framework of guided missile development in LAPAN, Center of Technology has been rocket designed, constructed and then performed a guided missile trial launching in Pameungpeuk in May 2002. However the result was still far from expectation. It has been realized that numerous of factors played a part in the failure of the missile trial launching, which are structure strenght, propulsion, propellant, guidance system and aerodynamic stability. From all the above factors, aerodynamic static stability is the initial requirement which has to be validated before stepping to the next design process. Based on the above situation, it has been carried out a analysis un RKX 250 rocket aerodynamic static stability with canard guidance which configuration is almost similiar with the one that was launched in Pameungpeuk. To find out the rocket's aerodynamic static stability, a research on lift coefficient and drag coefficient must be done first. From the lift coefficient data, a conduction the center pressure of aerodynamics rocket. Method that is used in this research is the ine which was developed by quadrature multhopp which is analytical method (Krasnov N.F.1978).